Assessing the Influence of Social Media Food Vlog Content on Students’ Sustainable Food Waste Management Practices: A Mixed-Methods Approach - Regie Boy B. Fabro; Divina Paula J. Rios (Future Science / FSH-PH Publications, 2026)
This study examines the influence of social media food vlog content on students’ attitudes and practices regarding sustainable food waste management and the 3Rs (Reduce, Reuse, Recycle) in a public secondary high school in the Ilocos Region, Philippines. Food waste is a significant issue in the country, particularly in schools, where large student populations contribute to the problem. With the growing use of social media among Filipino students, this research explores its potential as a tool to promote sustainable food waste management practices. A mixed-methods approach was employed, collecting data from 66 Senior High School students through surveys and focus group discussions. Quantitative data was analyzed using descriptive statistics and Pearson’s correlation to examine the relationship between students’ exposure to social media content and their 3Rs practices. Thematic analysis of qualitative data explored emotional and motivational factors influencing behavior. Results show that students are moderately exposed to sustainability-related social media content, with platforms like Facebook, TikTok, and YouTube as primary sources. Social media content creators positively shape students’ attitudes, increasing awareness, motivation, and confidence. However, students’ engagement often remains passive, with a gap between awareness and consistent 3Rs practices. Emotional and motivational factors, such as feelings of inspiration, guilt, peer influence, and a desire to make a difference, are key drivers of sustainable behavior.